The lived experiences of African American women mentors : what it means to guide as community pedagogues - Gamble-Lomax, Wyletta (Race and education in the twenty-first century., 2016)
This book explores the lived experiences of six African American female mentors working with African American female youth. Through philosophical and pedagogical lenses, Gamble-Lomax brings new understanding to African American female experiences and how they connect to today's educational climate.